Invariant natural killer T cells play dual roles in the development of experimental autoimmune uveoretinitis. (December 2016) - Satoh, Masashi; Namba, Ken-ichi; Kitaichi, Nobuyoshi; Endo, Noriko; Kitamei, Hirokuni; Iwata, Daiju; Ohno, Shigeaki; Ishida, Susumu; Onoé, Kazunori; Watarai, Hiroshi; Taniguchi, Masaru; Ishibashi, Tatsuro; et al.
Abstract: Experimental autoimmune uveoretinitis (EAU) represents an experimental model for human endogenous uveitis, which is caused by Th1/Th17 cell-mediated inflammation. Natural killer T (NKT) cells recognize lipid antigens and produce large amounts of cytokines upon activation. To examine the role of NKT cells in the development of uveitis, EAU was elicited by immunization with a peptide from the human interphotoreceptor retinoid-binding protein (hIRBP1-20 ) in complete Freund's adjuvant and histopathology scores were evaluated in C57BL/6 (WT) and NKT cell-deficient mice. NKT cell-deficient mice developed more severe EAU pathology than WT mice. When WT mice were treated with ligands of the invariant subset of NKT cells (α-GalCer or RCAI-56), EAU was ameliorated in mice treated with RCAI-56 but not α-GalCer. IRBP-specific Th1/Th17 cytokines were reduced in RCAI-56-treated compared with vehicle-treated mice. Although the numbers of IRBP-specific T cells detected by hIRBP3-13 /I-A b tetramers in the spleen and the draining lymph node were the same for vehicle and RCAI-56 treatment groups, RORγt expression by tetramer-positive cells in RCAI-56-treated mice was lower than in control mice. Moreover, the eyes of RCAI-56-treated mice contained fewer IRBP-specific T cells compared with control mice. These results suggest that invariant NKT (iNKT) cells suppress the induction of Th17 cells and infiltration of IRBP-specific T cells into the eyes, thereby reducing ocular inflammation. However, in sharp contrast to the ameliorating effects of iNKT cell activation during the initiation phase of EAU, iNKT cell activation during the effector phase exacerbated disease pathology. Thus, we conclude that iNKT cells exhibit dual roles in the development of EAU. Highlights: Autoimmune ocular inflammation is aggravated in NKT cell-deficient mice. Activation of iNKT cells by RCAI-56 on immunization ameliorates EAU. RCAI-56 stimulates iNKT cells to produce IFN-γ, that lead reduction of autoreactive Th17 cells. RCAI-56 also suppresses the recruitment of autoreactive T cells in the eyes.